ROCAMEX V21 AND ROCAMEX VS101 NEW IMPROVED EARLY VARIETIES OF CORN FOR THE MESA CENTRAL - WELLHAUSEN, EJ; ROSA PALACIOS, GILBERTO DE LA; ROBERTS, LM; RIOS CUEVAS, ATANASIO (Hospital General, CD MEXICO, DF, MEX, 1979)
Grain sorghum (Sorghum vulgare), a highly productive crop for regions of low rainfall, has been under investigation by the Office of Special Studies, S A G, since 1944 More than 250 vars, hybrids, or strains have been grown in expts to determine ada
PHYS REV B
Keywords: ROCAMEX V 21, ROCAMEX VS 101: NEW IMPROVED, EARLY VARIETIES OF CORN, MESA CENTRAL; CIENCIAS DE LA VIDA; BIOLOGIA VEGETAL; BOTANICA GENERAL